Digital Payment Paradox: Pengaruh Transaksi Non-Tunai Terhadap Pengelolaan Keuangan Mahasiswa Universitas Khairun Ternate - Kholifatus Saniyah; Nitika Florasita Bungan; Eka Susika Batawi; Fitriyani Abdurahman (MAMEN: Jurnal Manajemen, 2026)
The rapid advancement of financial technology has altered college students' consumption patterns through the massive adoption of cashless transactions. However, this convenience often presents a paradox that deteriorates personal financial behavior control due to the reduction of the psychological sensation when spending money (low pain of payment). This study aims to analyze the influence of cashless transaction usage on the financial management of students at Universitas Khairun Ternate. An associative quantitative approach was employed using a survey method with structured questionnaires. Data were analyzed using the Simple Linear Regression technique after meeting the required classic assumption tests (normality and heteroscedasticity tests). The research findings reveal that cashless transactions have a significant negative effect on student financial management  thitung = -2.446; Sig = 0.016 < 0.05. The R Square value of 5.8% indicates that although the effect is significant, the majority of the variation in  tudents' financial management is driven by other factors outside this research model. These results confirm the existence of a digital payment paradox, wherein financial digitalization inadvertently diminishes the quality of students' financial governance due to the loss of physical budgetary control.